2014
DOI: 10.1159/000363771
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Continuity in Inhaler Device Choice for Asthma and Chronic Obstructive Pulmonary Disease

Abstract: Inhaled therapies are central to the treatment of asthma and chronic obstructive pulmonary disease. Physicians consider many factors when selecting the most appropriate inhaler device, including device efficacy and the cost to the health care system. This review aims to discuss the factors that are important when considering inhaler devices and the importance of continuity in the choice of inhaler device.A large number of factors can contribute to therapeutic outcomes with inhalation devices. The inhalation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
2
48
2
3
Order By: Relevance
“…In concordance with our findings, Thomas and co‐workers have shown that real‐world asthma outcomes vary depending on the device, suggesting that devices are not interchangeable . In a recently published work, it is recommended that patients with stable disease should remain on their current device . This has also been stated in ERS/ISAM taskforce report .…”
Section: Discussionsupporting
confidence: 88%
“…In concordance with our findings, Thomas and co‐workers have shown that real‐world asthma outcomes vary depending on the device, suggesting that devices are not interchangeable . In a recently published work, it is recommended that patients with stable disease should remain on their current device . This has also been stated in ERS/ISAM taskforce report .…”
Section: Discussionsupporting
confidence: 88%
“…Suboptimal adherence and inhaler mishandling have adverse effects on disease control, while satisfaction with inhaler devices is associated with improved adherence, improved clinical outcomes and reduced cost [911]. In turn, devices associated with the lowest numbers of handling errors have the highest patient preference ratings [12,13], suggesting that a patient’s acceptance of a device may be correlated with ease of handling.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal inhaler technique 7 and inhaler mishandling 8 are still common in real-life use, and lack of device continuity may increase these problems. 9,10 By the availability of many new products, using different devices to deliver drugs to the lungs, asthma and COPD patients are likely to be exposed to more than one type of inhaler during their treatment journey, potentially also concurrently.…”
Section: Introductionmentioning
confidence: 99%